Pengaruh Pencatatan Sustainability Report terhadap Produktivitas Sumber Daya dan Pertumbuhan Ekonomi di PT Unilever Indonesia Tbk - Rahmadani, Fitra (Business and Investment Review, 2023)
Abstract. The recording of a Sustainability Report has become one of the primary approaches in modern businesses aiming to measure, track, and communicate the social, environmental, and economic impacts of a company. This research aims to analyze the influence of recording the Sustainability Report on resource productivity and economic growth at PT Unilever Indonesia Tbk. Through a methodology involving historical data analysis and detailed evaluation models, this study investigates how the implementation of the Sustainability Report within the company influences resource productivity in day- to-day operations. This research provides a foundation for a deeper understanding of the importance of maintaining a Sustainability Report in enhancing the productivity and economic growth of the company, along with its implications within the context of a sustainable economy. Abstrak. Pencatatan Sustainability Report telah menjadi salah satu pendekatan utama dalam bisnis modern yang bertujuan untuk mengukur, melacak, dan mengomunikasikan dampak sosial, lingkungan, dan ekonomi suatu perusahaan. Penelitian ini bertujuan untuk menganalisis pengaruh pencatatan Sustainability Report terhadap produktivitas sumber daya dan pertumbuhan ekonomi di PT Unilever Indonesia Tbk.. Melalui metodologi analisis data historis dan model evaluasi terperinci, penelitian ini menyelidiki bagaimana implementasi Sustainability Report di perusahaan memengaruhi produktivitas sumber daya dalam operasional sehari-hari. Penelitian ini memberikan landasan untuk pemahaman lebih lanjut tentang pentingnya pencatatan Sustainability Report dalam meningkatkan produktivitas dan pertumbuhan ekonomi perusahaan, serta implikasinya dalam konteks ekonomi yang berkelanjutan. Kata kunci: Sustainability Report, produktivitas sumber daya, pertumbuhan ekonomi, PT Unilever Indonesia Tbk.